PO 124 - Edema agudo do pulmão por pressão negativa – Raro mas subdiagnosticado - Gonçalves, Pedro; Aguiar, Ana Rita; Ferreira, Leonardo; Pinto, Sérgio; Miranda, Rita; Teles, Ana Rita (Journal of the Portuguese Society of Anesthesiology, 2023)
x